2017
DOI: 10.1002/hep.28873
|View full text |Cite
|
Sign up to set email alerts
|

Expression of scavenger receptor‐AI promotes alternative activation of murine macrophages to limit hepatic inflammation and fibrosis

Abstract: The liver maintains an immunologically tolerant environment as a result of continuous exposure to food and bacterial constituents from the digestive tract. Hepatotropic pathogens can take advantage of this niche and establish lifelong chronic infections causing hepatic fibrosis and hepatocellular carcinoma. Macrophages (Mϕ) play a critical role in regulation of immune responses to hepatic infection and regeneration of tissue. However, the factors crucial for Mϕ in limiting hepatic inflammation or resolving liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…Although MSR1 has been implicated in recognition of viral nucleic acids, activation of type I interferon 4, 5 , macrophage adherence 6 , M2 macrophage polarization 7 , and activation of neutrophil-mediated complement 8 , its molecular mechanism of action remains elusive. In the current study, we demonstrate a critical role for MSR1 in controlling CHIKV pathogenesis and provide several lines of evidence showing how MSR1 participates in autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although MSR1 has been implicated in recognition of viral nucleic acids, activation of type I interferon 4, 5 , macrophage adherence 6 , M2 macrophage polarization 7 , and activation of neutrophil-mediated complement 8 , its molecular mechanism of action remains elusive. In the current study, we demonstrate a critical role for MSR1 in controlling CHIKV pathogenesis and provide several lines of evidence showing how MSR1 participates in autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…CHIKV was propagated in Vero cells to a titer of ∼10 7 plaque forming units (PFU)/ml and prepared in 50µl of sterile 1% gelatin in phosphate buffered saline (PBS) for injection. Briefly, age-and sex-matched wild type and specific gene deleted mice (>8 weeks old) were infected with 5×10 4 PFU of La Reunion strain LR2006-OPY1 at the ventral side of a hind foot subcutaneously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that MerTK activation leads to inhibition of the mTOR pathway and SR-A1-mediated activation of macrophages (44). Inhibition of the mTOR pathway enhances the effects of pro-inflammatory cytokines via NF-κB in phagocytic cells after bacterial stimulation (45) and of caspase-1 during endotoxin-mediated shock (46).…”
Section: Discussionmentioning
confidence: 99%
“…4B). The macrophage polarization was further investigated using real-time PCR and western blot for the prototypical M1 and M2 markers, inducible nitric oxide synthase (iNOS) and Arg-1 [42]. When cultured in DFSC-CM with LPS stimuli, macrophages exhibited significant upregulation of Arg-1 and downregulation of iNOS, whereas macrophages cultured in Ham's F-12K medium with LPS infection expressed high levels of iNOS but not Arg-1 at both the transcriptional and translational levels (Fig.…”
Section: Dfsc-cm Induced M2 Macrophage Polarizationmentioning
confidence: 99%